(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
In connection with the granting of academic, organizational management and financial independence to state higher education institutions, the article provides them with the authority to independently dispose of financial resources, independently determine the amount of the payment contract, and determine the amount of wages for teaching staff.